(untitled) (Ozone Therapy Global Journal, 2020)
COVID-19 forced us to change plans, projects, routines and even ways of making medicine; including how to approve drugs that did not meet the conditions of safety and efficacy, which are supposedly required of all products intended to treat diseases of human beings. According to the different WHO (World Health Organization) communiqués issued since the start of the pandemic, we should all be very clear about two points that are the indelible marks of the challenge posed by the pandemic to health science: (1) The COVID-19 virus has characteristics quite unknown, and with a speed of mutability frankly different from other viruses. (2) There is still no "magic potion" from previous centuries, called today a "vaccine" that can effectively deal with the virus. The desperate career of pharmaceutical companies began in February 2020, in search of the "Holy Grail" that eliminates the pandemic, in order to continue climbing the ladder of scientific prestige, in addition to obtaining exorbitant profits from the supposed panacea of ​​what they discover.